1998
DOI: 10.1086/302167
|View full text |Cite
|
Sign up to set email alerts
|

The Ashkenazic Jewish Bloom Syndrome Mutation blmAsh Is Present in Non-Jewish Americans of Spanish Ancestry

Abstract: Bloom syndrome (BS) is more frequent in the Ashkenazic Jewish population than in any other. There the predominant mutation, referred to as "blmAsh," is a 6-bp deletion and 7-bp insertion at nucleotide position 2281 in the BLM cDNA. Using a convenient PCR assay, we have identified blmAsh on 58 of 60 chromosomes transmitted by Ashkenazic parents to persons with BS. In contrast, in 91 unrelated non-Ashkenazic persons with BS whom we examined, blmAsh was identified only in 5, these coming from Spanish-speaking Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 11 publications
2
45
0
4
Order By: Relevance
“…25 in a heterozygous or homozygous state were tested for the blm Ash mutation, they were found to be negative, showing that this haplotype predated the blm Ash mutation. Our results are in agreement with previous haplotype studies (Ellis et al 1998) that showed the presence of a predominant single haplotype (based on microsatellite markers surrounding BLM) considered to be the founder haplotype that blm Ash occurred in Ashkenazi Jews.…”
Section: Pilot Association Studiessupporting
confidence: 93%
See 2 more Smart Citations
“…25 in a heterozygous or homozygous state were tested for the blm Ash mutation, they were found to be negative, showing that this haplotype predated the blm Ash mutation. Our results are in agreement with previous haplotype studies (Ellis et al 1998) that showed the presence of a predominant single haplotype (based on microsatellite markers surrounding BLM) considered to be the founder haplotype that blm Ash occurred in Ashkenazi Jews.…”
Section: Pilot Association Studiessupporting
confidence: 93%
“…25) in the BLM gene, which appears to be the ancestral haplotype on which the blm Ash mutation occurred in the Ashkenazi Jewish population. Ellis et al (1998) using microsatellite data obtained similar association results. However, the stability of SNP sites offers opportunities to estimate the age of such disease mutations more precisely.…”
Section: Pilot Association Studiessupporting
confidence: 56%
See 1 more Smart Citation
“…Although recent converts were not legally permitted to travel to the New World, it has been argued that many in fact made the journey. Interestingly, the analysis of Y chromosome data and rare disease mutations are consistent with a genetic contribution from North Africa and the Middle East to the ancestry of Ibero-Americans (15,26,35,65,100).…”
Section: Subcontinental Ancestrymentioning
confidence: 52%
“…39 This suggests the possibility that contemporary Ashkenazi mtDNA diversity may derive, in part, from a small and subdivided ancestral mtDNA gene pool, and is consistent with the hypothesis that some high frequency disease alleles originated before the separation of Jewish communities in the Near East. 40,41 Indeed, estimates of the age of mutations causing Ashkenazi genetic diseases range from recent times (ie, during demographic upheavals within Europe in the past 500 years), 6,26,40,42 to times when ancestral Ashkenazi populations were first migrating to and within Europe, 43 to times before Jewish populations migrated out of the Near East. 40,44,45 …”
Section: Discussionmentioning
confidence: 99%